A Qualitative Approach to the Benefits of Meditation for Elderly Health - Putu Pranindya Maheswari (Jurnal Multidisiplin Indonesia, 2026)
Background: Analyzing the health benefits of meditation for the elderly through a qualitative approach, this study aims to provide readers with insights into the health benefits gained through meditation.The increase in life expectancy has led to a growing elderly population prone to physical and mental health decline, such as stress, sleep disturbances, and chronic diseases (Hypertension, etc.). Meditation is known as a promising non-pharmacological intervention to improve the quality of life. This study aims to deeply and holistically explore (qualitatively) the subjective experiences and meanings perceived by the elderly regarding the practice of meditation and its impact on their health.Method: The method used is qualitative by comparing several books and journals. Results: Several main themes regarding the benefits of meditation were found: 1) Enhanced Emotional Well-being (sense of calm, reduced anxiety and stress); 2) Improved Physical Quality (better sleep quality, reduced Hypertension symptoms, increased energy); 3) Strengthening Spiritual Aspects (gratitude, feeling closer to God, life optimism); and 4) General Improvement in Quality of Life (more harmonious social relations). Conclusion: Meditation provides significant holistic benefits for elderly health, encompassing physical, emotional, and spiritual aspects. These findings underscore the importance of incorporating meditation as a coping strategy and non-medical health promotion for the elderly population.